Plasminogen Activator System in Periodontal Disease - Méndez Visag, Christian (2012)
The plasminogen activator system is actively involved in periodontal disease dynamics and is finely balanced in terms of their activators and inhibitors, although there are periods where exacerbation of periodontal pockets can break the delicate balance between activators (t-PA) and inhibitors of plasminogen (PAI-2) triggering the progression of periodontal disease include the participation of bacterial pathogens Porphyromonas gingivalis as characterized by generating the major imbalance between activators and inhibitors with a consequent increase in fibrinolytic activity. The effects of the imbalance of the constituents of plasminogen activator system in particular t-PA takes on more importance in the gingival level bleeding events in patients with deficiencies of coagulation factors such as warfarin anticoagulation or severe liver disease such as cirrhosis.The plasminogen activator system as part of the fibrinolytic system is described by the relevant literature regarding their involvement in the pathogenesis of periodontal disease and its components are described comparatively local or periodontal level with systemic level.